Government corruption and foreign direct investment under the threat of expropriation - Christopher Hajzler; Jonathan Rosborough (Bank of Canada, 2016)
Foreign investment is often constrained by two forms of political risk: expropriation and corruption. We examine the role of government corruption in foreign direct investment (FDI) when contracts are not fully transparent and investors face the threat of expropriation. Using a novel dataset on worldwide expropriations of FDI over the 1990-2014 period, we find a positive relationship between the extent of foreign investor protections and the likelihood of expropriation when a country's government is perceived to be highly corrupt, but not otherwise. We then develop a theory of dynamic FDI contracts under imperfect enforcement and contract opacity in which expropriation is a result of illicit deals made with previous governments. In the model, a host-country government manages the FDI contract on behalf of the public, which does not directly observe government type (honest or corrupt). A corrupt type is able to extract rents by encouraging hidden investments in return for bribes. Opportunities for corrupt deals arise from the distortions in the optimal contract when the threat of expropriation is binding. Moreover, a higher likelihood of the government being corrupt increases the public's temptation to expropriate FDI, magnifying investor risk. The model predicts that expropriation is more likely to occur when the share of government take is low and following allegations of bribes to public officials, and it suggests an alternative channel through which corruption reduces optimal foreign capital flows.
Keywords: F23; F21; F34; 330; International topics; Development economics; Economic models